A Series of Mesoporous Metal‐Organic Frameworks with Tunable Windows Sizes and Exceptionally High Ethane over Ethylene Adsorption Selectivity. (7th September 2020) - Lysova, Anna A.; Samsonenko, Denis G.; Kovalenko, Konstantin A.; Nizovtsev, Anton S.; Dybtsev, Danil N.; Fedin, Vladimir P.
Abstract: The NIIC‐20 (NIIC stands for Nikolaev Institute of Inorganic Chemistry) is a family of five isostructural metal‐organic frameworks (MOFs) based on dodecanuclear wheel‐shaped carboxylate building blocks {Zn12 (RCOO)12 (glycol)6 } (glycol is deprotonated diatomic alcohol: ethylene glycol, 1, 2‐propanediol, 1, 2‐butanediol, 1, 2‐pentanediol or glycerol), quantitatively crystallized from readily available starting chemicals. The crystal structures contain large mesoporous cages of 25 Å connected through Zn12 rings, of which inner diameter and chemical nature depend solely on the chosen glycol. The NIIC‐20 compounds feature high surface area and rarely observed inversed adsorption affinity for saturated hydrocarbon (ethane) over the unsaturated ones (ethylene, acetylene). The corresponding IAST (Ideal Adsorbed Solution Theory) adsorption selectivity factors reach as much as 15.4 for C2 H6 /C2 H4 and 10.9 for C2 H6 /C2 H2 gas mixtures at ambient conditions, exceeding those for any other porous MOF reported so far. The remarkable combination of high adsorption uptakes and high adsorption selectivities makes the NIIC‐20 series a new benchmark of porous materials designed for ethylene separation applications. Abstract : A series of five isostructural metal‐organic frameworks (NIIC‐20) features large mesoporous cages connected through smaller windows, which diameter and chemical environment could be altered, affecting the gas adsorption properties. NIIC‐20 demonstrates unusual inversed selectivity for saturated hydrocarbons (C2 H6 ) over unsaturated ones (C2 H4, C2 H2 ) exceeding the known literature data.